Corrosion behavior of pipeline steel with different microstructures under AC interference in acid soil simulation solution - Zhu, Meijiao (2021)
Corrosion behavior of X65 pipeline steels with different microstructures under alternating current (AC) interference was investigated in acid soil simulation solution by potentiodynamic polarization curve, potentiostatic polarization curve and immersion test. The results show that superimposed AC causes a sharp increase in corrosion current density of X65 steel. With the increase in i , the corrosion current densities of steels with various microstructures increase, especially at high i . Hot-rolled steel mainly experiences uniform corrosion, with very slight pit corrosion. Serious corrosion degrees with intensive corrosion pits can be observed on the surfaces of normalized and quenched microstructure steels. The annealed steel exhibits the feature of non-uniform corrosion with some pitting. The steels with various microstructures applied with AC have different corrosion resistance. The normalized steel shows the worst corrosion resistance, then the quenched microstructure, and the hot-rolled steel displays the optimum corrosion resistance. The difference in the microstructure can result in difference in corrosion degree and occurrence position of pitting corrosion of X65 steel. The normalized microstructure composed of polygonal ferrite and a large amount of pearlite and bainite is the most susceptible to AC corrosion. AC AC